Analysis of bistatic scattering behavior of natural surfaces - Dubois-Fernandez, Pascale; Cantalloube, Hubert; du Plessis, Oliver Ruault; Wendler, Michael; Vaizan, Bernard; Coulombeix, Colette; Heuze, Daniel; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2004)
Bistatic configuration is an attractive concept for spaceborne and airborne missions for several reasons. The first one is the important cost reduction achieved over the multiple radar constellation, by having only one transmitter (expensive part) and multiple receivers. The most promising applications are single pass interferometry with a large baseline and target or surface characterization from bistatic scattering signature analysis. In a Defense context, the improved furtivity associated with the receive-only component can provide a wider operational capability. In order to explore the challenges associated with bistatic radar, DLR and ONERA organized a joint bistatic airborne experiment involving E-SAR and RAMSES. After the pre-flight engineering analysis phase, necessary to understand how to work the two radars jointly and resolve the technical challenges associated with the acquisition like the synchronization of the two systems, two flights were planned over an area in southern of France (Nîmes). Several innovative configurations were tested. An active transponder from DLR and a set of passive corner reflectors were also deployed on the test area for calibration of the monostatic and bistatic data. Two main geometrical configurations were flown to explore two scientific objective· to simulate the cartwheel/pendulum concept (single pass interferometry with a large baseline), · to evaluate the improved target characterization provided by the bistatic geometry. In this paper, we analyze the influence of the bistatic angle on the images and on the scattering of natural. This will need to be compared with a similar analysis on incidence angle agility.
DLR Import::2019-04-03